Comparing the clinical outcomes of Remdesivir and Interferon beta-1a in hospitalized COVID-19 patients: A cross-sectional retrospective single-center study - Asgari, Mehrdad; Kousha, Abolfazl; Ghaffari, Mohammad Ebrahim; Yaghubi Kalurazi, Tofigh; Zaminy, Arash (The Journal of Infection in Developing Countries, 2025)
Introduction: The effectiveness of remdesivir (RDV) and interferon beta-1a (IFNβ-1a) was assessed and compared in patients hospitalized with coronavirus disease of 2019 (COVID-19). Methodology: A total of 162 hospitalized COVID-19 patients were divided into two groups: the RDV group and the IFNβ-1a group. Through laboratory tests and a physical examination, the patient's clinical condition was evaluated. Results: RDV and IFNβ-1a treatments significantly decreased fever, cough, shortness of breath, and weakness in COVID-19 patients (All p < 0.001). RDV treatment significantly decreased shortness of breath, erythrocyte sedimentation rate (ESR), and creatinine, relative to IFNβ-1a treatment (p < 0.03, p = 0.001, and p < 0.004, respectively). RDV treatment significantly decreased Lactate Dehydrogenase (LDH) in COVID-19 patients (p = 0.006). The mean time of hospitalization was 8.9 days in the RDV group and 8.2 days in the IFNβ-1a group. There was no statistical difference between the two groups. The IFNβ-1a group had a considerably lower rate of intensive care unit (ICU) admission than the RDV group (p = 0.006). Conclusions: No difference in clinical outcomes was found between RDV and IFNβ-1a treatments. RDV was more effective than IFNβ-1a in moderating the inflammatory response in COVID-19 patients by reducing LDH and ESR. The IFNβ-1a group had a considerably lower rate of ICU admission than the RDV group.